Data underpinning research article "Techno-environmental analysis of battery storage for grid level energy services" - Chowdhury, Jahedul; Balta-Ozkan, Nazmiye; Goglio, Pietro; Hu, Yukun; Varga, Liz; McCabe, Leah (Cranfield University, 2020)
This file includes data from the National Grid, UK for electricity supply and demand which was modified according to the research methodology laid out in the paper here (https://doi.org/10.1016/j.rser.2020.110018). Also, all the data needed for reproducing figures presented in the journal article are also included in the data file.
Keywords: 'Battery energy storage system (BESS)'; 'CCGT'; 'LCA'; 'Peak demand management'; 'renewable integration'; 'Energy Generation; Conversion and Storage Engineering'